Synthesis of the cyanobacterial metabolite nostodione A, structural studies and potent antiparasitic activity against Toxoplasma gondii. Issue 39 (20th August 2015) - McNulty, James; Keskar, Kunal; Jenkins, Hilary A.; Werstiuk, Nick H.; Bordón, Claudia; Yolken, Robert; Jones-Brando, Lorraine
Abstract : A total synthesis of the cyanobacterial natural product nostodione A is reported involving a convergent, diversity-oriented route, enabling the assembly of a mini-library of structural analogues. Abstract : A total synthesis of the cyanobacterial natural product nostodione A is reported involving a convergent, diversity-oriented route, enabling the assembly of a mini-library of structural analogues. The first single crystal X-ray structural determination on a member of this series is reported along with SAR studies identifying potent inhibitors of invasion and replication of the parasitic protozoan Toxoplasma gondii .